Pengembangan Media Pembelajaran Digital Berbasis STEM pada Materi Wujud Zat dan Perubahannya Untuk Meningkatkan Pemahaman Sains Siswa Kelas IV SD - Alfie Kurnia, Lady; Widi Winarni, Endang; Muktadir, Abdul (UNIB Press, 2025)
The purpose of this study was to develop STEM-based digital learning media on the material of the form of substances and their changes to improve science understanding. The type of research used is Research and Development (R&D) research using the ADDIE model. The type of data used is quantitative and qualitative data, namely quantitative data is using a questionnaire assessment score given by the validator while qualitative data is comments and suggestions from the validator. Based on the results of the study, it is obtained that the characteristics of learning media contain elements of science in the material, technology in the use of media, engineering in group assignments and mathematics in the evaluation. The feasibility of learning media based on material expert validation obtained a score of 0.83, language validation of 0.83 and design validation of 0.67. User response to students obtained a percentage of 93%. The pretest results obtained a score of 45.25, while the posttest results obtained a score of 87.5. The results of the N-Gain test based on science understanding in the aspect of cognitive level facts C1 by 64% and C2 by 88%, while in the aspect of cognitive level concepts C3 obtained a percentage of 83%. Based on this, the use of STEM-based digital learning media on the material of the form of substances and their changes can improve scientific understanding has increased significantly.